LEVERAGING INFORMATION TECHNOLOGY TO REVOLUTIONIZE DENTAL INSURANCE AND PROMOTE ORAL HEALTH - Pravesh Nikhare, (INTERNATIONAL JOURNAL OF RESEARCH IN COMPUTER APPLICATIONS AND INFORMATION TECHNOLOGY (IJRCAIT), 2024)
This article explores the transformative role of Information Technology (IT) in revolutionizing the dental insurance industry and promoting oral health. It examines how dental insurers are leveraging advanced IT solutions, including artificial intelligence, teledentistry, blockchain, and data analytics, to create a more proactive and patient-centered approach to oral health management. The article discusses five key areas where IT is making significant impacts: educating and empowering patients through online portals and interactive tools; incentivizing preventive care with data-driven reward programs and personalized incentives; enabling early detection of dental issues through advanced data analytics and targeted preventive campaigns; promoting access to care via teledentistry solutions and streamlined appointment systems; and fostering collaboration among stakeholders through interoperable electronic health records and enhanced claims processing. By integrating these technological advancements, dental insurers are positioned to improve oral health outcomes, reduce healthcare costs, and contribute to a healthier society.